2019
DOI: 10.1111/den.13393
|View full text |Cite
|
Sign up to set email alerts
|

Objective validity of the Japan Narrow‐Band Imaging Expert Team classification system for the differential diagnosis of colorectal polyps

Abstract: Background and Aim The Japan Narrow‐Band Imaging (NBI) Expert Team (JNET) classification is a recently proposed NBI magnifying endoscopy‐based classification system for colorectal tumors. Although the usefulness of this system has been reported by JNET experts, its objective validity remains unclear. We tested its validity and usefulness for the diagnosis of colorectal polyps by including colonoscopy experts and non‐experts as test participants. Methods Forty NBI images of polyps of various JNET types were sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 19 publications
(25 reference statements)
1
20
0
1
Order By: Relevance
“…In our cohort, we confirm that after complete ER, a recurrence may be found in almost one-quarter of patients, but is endoscopically manageable in the majority of cases. Even if our median endoscopic follow-up was relatively short (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)), data from the literature are reassuring because 96 % of recurrences occur within 6 months after index resection, and only 2 % of recurrences can be expected after 12 months [34], as also suggested by our median time-to-recurrence of 7 months (IQR 4-13). Our multivariate analysis identified independent predictors of recurrence, both known (PM vs EB resection) and poorly reported (grading of dysplasia and involvement of "risky hotspots").…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In our cohort, we confirm that after complete ER, a recurrence may be found in almost one-quarter of patients, but is endoscopically manageable in the majority of cases. Even if our median endoscopic follow-up was relatively short (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)), data from the literature are reassuring because 96 % of recurrences occur within 6 months after index resection, and only 2 % of recurrences can be expected after 12 months [34], as also suggested by our median time-to-recurrence of 7 months (IQR 4-13). Our multivariate analysis identified independent predictors of recurrence, both known (PM vs EB resection) and poorly reported (grading of dysplasia and involvement of "risky hotspots").…”
Section: Discussionsupporting
confidence: 61%
“…Irregularity in superficial pit/vascular pattern seems to be the strongest SMI predictor. However, JNET classification was not available for all lesions, and published experiences have demonstrated that interobserver agreement is suboptimal, with specific training required to reach acceptable accuracy [21,31,32]. This could suggest that if the endoscopist has sufficient training/experience with pit/ vascular pattern interpretation, this should be the most considered parameter, along with presence of pseudodepression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional white-light endoscopy (WLE) is a fundamental modality, but magnification endoscopy is not necessarily globally used due to a requirement for technical expertise. Magnification chromoendoscopy with crystal violet staining (CV-MCE) enables visualization of the pit pattern (the shape of the glandular crypt opening) [3][4][5], and magnification endoscopy with narrow-band imaging (NBIME) enables visualization of the vessel pattern without mucosal staining [6][7][8]. Generally, magnification endoscopy is considered to be superior to WLE for the qualitative diagnosis of colorectal polyps, but it has not been investigated fully.…”
Section: Introductionmentioning
confidence: 99%